Порождающие паттерны проектирования в компьютерной лингвистике: Factory Method, Prototype, Singleton - Никоненко, А.А. (Кибернетика и системный анализ, 2012)
Розглянуто питання використання породжуючих паттернів для розв’язання задач комп’ютерної лінгвістики. Наведено огляд основних властивостей паттернів Factory Method, Prototype, Singleton, суть та особливості використання, проведено порівняльний аналіз даної трійки з іншими породжуючими паттернами. Розглянуто структуру паттернів та можливості їх застосування в програмних системах при розв’язанні прикладних задач комп’ютерної лінгвістики. Для кожного паттерна наведено умови, за яких його використання є найбільш доцільним. The paper analyzes the use of creational patterns in solving computational linguistics problems. The Factory Method, Prototype, and Singleton patterns are considered in detail. The basic properties of patterns and the nature and characteristics of their use are reviewed, and the comparative analysis with other creational patterns is carried out. The structure of patterns and their possible applications in software systems to solve computational linguistics problems is considered separately. For each pattern, the conditions are presented under which its use is most appropriate.